2023
DOI: 10.2217/cer-2022-0091
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of progressive supervised and home program exercise therapy in mild–moderatehallux valgus

Abstract: Aim: To compare the effects of progressive exercise therapy, performed under the supervision of a physiotherapist and given as a home program in individuals with hallux valgus. Methods: Participants were randomly divided into two groups. While one group performed the exercises under the supervision of a physiotherapist, the other group did the same program at home. Results: The amount of decrease in foot adduction angle, pain level while walking, and right foot navicular height of individuals receiving treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
0
3
0
5
Order By: Relevance
“…In a previous study, Mickle et al [14] reported very high adherence (89%) with this program, although this involved face-to-face group exercise classes. Group exercise is more effective than home based exercises for hallux valgus [45], but this was not feasible in the current study and is di cult to maintain beyond a trial [46]. Participants found the exercise program quite challenging, and although many were housebound for much of the study due to COVID-19-related stay-at-home restrictions, they generally found it di cult to incorporate the program into their daily routine.…”
Section: Discussionmentioning
confidence: 94%
“…In a previous study, Mickle et al [14] reported very high adherence (89%) with this program, although this involved face-to-face group exercise classes. Group exercise is more effective than home based exercises for hallux valgus [45], but this was not feasible in the current study and is di cult to maintain beyond a trial [46]. Participants found the exercise program quite challenging, and although many were housebound for much of the study due to COVID-19-related stay-at-home restrictions, they generally found it di cult to incorporate the program into their daily routine.…”
Section: Discussionmentioning
confidence: 94%
“…Com o objetivo de comparar os efeitos da terapia de exercícios progressivos realizados no domicílio com os realizados sob supervisão fisioterapêutica, o estudo incluiu 35 participantes entre 18 e 64 anos, com HV leve a moderado bilateralmente. Entretanto, os participantes foram incluídos desde que não tivessem recebido atendimento fisioterapêutico para HV nos últimos 6 meses e não tivessem usado aparelhos ortopédicos ou talas dinâmicas (OZTARSU; OKSUZ, 2023).…”
Section: Resultsunclassified
“…Quanto aos métodos de avaliação, foram usados: o ângulo do hálux foi avaliado pela goniometria, a dor pela Escala Visual Analógica (EVA), a cinesiofobia pela escala TAMPA, o equilíbrio estático por meio do teste de apoio unipodal, o equilíbrio dinâmico pelo teste de equilíbrio em Y, a capacidade funcional foi avaliada por meio do teste de 6 minutos (TC6), o Foot Function Index foi usado para avaliar os efeitos do HV quanto à dor, incapacidade e limitação de atividades, a SF-36 para avaliar a qualidade de vida geral dos indivíduos e a altura do navicular foi medida (OZTARSU; OKSUZ, 2023).…”
Section: Resultsunclassified
See 2 more Smart Citations